Milan's Potential for a Structured and Interactive Rurality. Issue 1 (2nd January 2017) - Orsini, Martina
ABSTRACT: A high proportion of Milan's wider metropolitan area is agricultural land, made up of farms of varying sizes and in various states of usage. Some of this land is open fields surrounding islands of densely built-up urban fabric, some is comprised of pockets or branches of space embedded within dense city fabric. Many farms in this area are highly productive, whilst many others are regularly being abandoned. Elements of open land now relate almost randomly to the city within a sprawl that has grown from what was once a coherent network of villages and towns. Now they have become absorbed into complex concentrations of relationships and co-existences between different urban fabrics, morphologies, and porosities, each subject to different dynamics of expansion and contraction. Since Italy's economic and social crisis of 2008, the growth of manufacturing in the area has been replaced by continued and possibly long-term shrinkage. In this situation, it is possible that a more coherent use of open land could play a key role in getting beyond the metropolitan area's current fragile and fragmented pattern of economic individualism and self-referentially programmed plots and buildings, a pattern that appears unable to adapt to the radical changes taking place. This paper argues that a strategic, spatial, and thematic reconceptualization of Milan's redundant open spaces and historic networks is a necessary step for the future planning and design of its urban territory.